Information Technology - New Generations 14th International Conference on Information Technology (Advances in Intelligent Systems and Computing,, 2018)
This volume presents a collection of peer-reviewed, scientific articles from the 14th International Conference on Information Technology - New Generations, held at the University of Nevada at Las Vegas on April 10-12, at Tuscany Suites Hotel in Las Vegas. The Book of Chapters addresses critical areas of information technology including web technology, communications, computing architectures, software engineering, security, and data mining.